Concurrent endurance and explosive type strength training increases activation and fast force production of leg extensor muscles in endurance athletes - Mikkola, J. S.; Rusko, H. K.; Nummela, A. T.; Paavolainen, L. M.; Häkkinen, K. (The Journal of Strength and Conditioning Research, 2007)
The purpose of this experiment was to examine the effects of concurrent endurance and explosive strength training on electromyography (EMG) and force production of leg extensors, sport-specific rapid force production, aerobic capacity, and work economy in cross-country skiers. Nineteen male cross-country skiers were assigned to an experimental group (E, n = 8) or a control group (C, n = 11). The E group trained for 8 weeks with the same total training volume as C, but 27% of endurance training in E was replaced by explosive strength training. The skiers were measured at pre and post training for concentric and isometric force-time parameters of leg extensors and EMG activity from the vastus lateralis (VL) and medialis (VM) muscles. Sport-specific rapid force production was measured by performing a 30-m double poling test with the maximal velocity (V30DP) and sport-specific endurance economy by constant velocity 2-km double poling test (CVDP) and performance (V2K) by 2-km maximal double poling test with roller skis on an indoor track. Maximal oxygen uptake (VO2max) was determined during the maximal treadmill walking test with the poles. The early absolute forces (0-100 ms) in the force-time curve in isometric action increased in E by 18 +/- 22% (p < 0.05), with concomitant increases in the average integrated EMG (IEMG) (0-100 ms) of VL by 21 +/- 21% (p < 0.05). These individual changes in the average IEMG of VL correlated with the changes in early force (r = 0.86, p < 0.01) in E. V30DP increased in E (1.4 +/- 1.6%) (p < 0.05) but not in C. The V2K increased in C by 2.9 +/- 2.8% (p < 0.01) but not significantly in E (5.5 +/- 5.8%, p < 0.1). However, the steady-state oxygen consumption in CVDP decreased in E by 7 +/- 6% (p < 0.05). No significant changes occurred in VO2max either in E or in C. The present concurrent explosive strength and endurance training in endurance athletes produced improvements in explosive force associated with increased rapid activation of trained leg muscles. The training also led to more economical sport-specific performance. The improvements in neuromuscular characteristics and economy were obtained without a decrease in maximal aerobic capacity, although endurance training was reduced by about 20%.